Determinación del nivel del caudal de agua y alternativas de conservación de la micro cuenca quebrada los monos, afluente del río Santa Rosa. - Ambuludi Pacheco, Fabian Aparicio (2016)
With the objective of determining the current situation of the flow of water in the micro Cuenca Hydrographical of the Gulch The Monkeys, belonging to the Parish Torata of the Canton Santa Rosa and actions that should be taken to maintain it, were carried out a work of applied investigation that it included the evaluation of the quality of the water and the characterization of the users.